2013
DOI: 10.2140/camcos.2013.8.99
|View full text |Cite
|
Sign up to set email alerts
|

A cartesian grid embedded boundary method for the compressible Navier–Stokes equations

Abstract: We present an unsplit method for the time-dependent compressible Navier-Stokes equations in two and three dimensions. We use a conservative, second-order Godunov algorithm. We use a Cartesian grid, embedded boundary method to resolve complex boundaries. We solve for viscous and conductive terms with a second-order semiimplicit algorithm. We demonstrate second-order accuracy in solutions of smooth problems in smooth geometries and demonstrate robust behavior for strongly discontinuous initial conditions in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Avenues to explore include allowing viscosity to vary with temperature and increasing the resolution of the grid. Separation is also observed in other numerical results (albeit for very different cases), yet is always very difficult to identify in experiment.…”
Section: Resultsmentioning
confidence: 67%
“…Avenues to explore include allowing viscosity to vary with temperature and increasing the resolution of the grid. Separation is also observed in other numerical results (albeit for very different cases), yet is always very difficult to identify in experiment.…”
Section: Resultsmentioning
confidence: 67%
“…For the compressible flow problem of the shock reflection from a wedge, we use the simulation parameters from Graves et al [14] shown in Table 3. As illustrated in Fig.…”
Section: Shock Reflection From a Wedgementioning
confidence: 99%
“…The second order, finite volume, strongly conservative Schwartz, et al algorithm [31] has been used in many larger applications, including incompressible Navier Stokes with moving boundaries [26], compressible Navier Stokes [15] and a DNA-transport application [37]. We compare our algorithm to the Schwartz, et al algorithm by comparing both eigenvalue spectrums and the how many degrees of freedom are required to achieve a given degree of accuracy.…”
Section: Prior Artmentioning
confidence: 99%
“…Previous conservative algorithms for embedded boundaries compute fluxes that are second order [28,26,31,13,15,27,9]. In those algorithms, the cell-averages of φ are approximated to second order by pointwise values at the centroids of faces, and fluxes are constructed by differencing those pointwise values.…”
Section: Underlying Analysismentioning
confidence: 99%